The Construction of Precursor Models in the Thinking of Young Children: The Case of Expansion and Contraction of Metals - Paraskevi Charalampopoulou; George Kaliampos; Konstantinos Lavidas; Konstantinos Ravanis (MDPI AG, 2023)
The aim of the current study is to examine how preschool children overcome their difficulties regarding thermal expansion and contraction and construct in their minds a precursor model; that is, an entity compatible with school knowledge. Having investigated these difficulties through a pretest, a teaching intervention was implemented based on both the telling of a fairy tale and the carrying out of experimental activities. Finally, the changes in children's thinking were studied with a posttest. The study involved 36 children aged 4-6 years who voluntarily participated in individual semistructured interviews conducted by three researchers in a special kindergarten setting. The results of the study revealed statistically significant progress in children's responses between pre- and posttests. Furthermore, the finding of almost 1/3 of children's responses being compatible with school knowledge indicates that (a) it is possible for children of that age to construct a precursor model for thermal expansion and contraction and (b) the combination of storytelling along with experimental activities is probably an appropriate teaching strategy.